Efektivitas Penggunaan QRIS Dalam Pembayaran Pajak Bumi dan Bangunan (PBB) - Syafi'i, Achmad; Arisyahidin, Arisyahidin; Maheri Laksono, Sonny Subroto (Universitas Islam Kadiri, 2026)
This study aims to analyze the effectiveness of QRIS use in Land and Building Tax (PBB) payments and its impact on achieving revenue targets in Kediri Regency. The research methods used included observation, interviews, and analysis of PBB transaction data through the QRIS system. The results show that the use of QRIS has proven effective in facilitating the public's PBB payments. QRIS enables transactions through various digital channels, speeds up the payment process, reduces queues at the counter, and improves the accuracy and transparency of transaction recording through integration with the Kediri Regency Bapenda tax information system. Although there were technical obstacles such as failed transactions or expired QRIS, these problems were overcome through data reconciliation, coordination with banks, and taxpayer education. In addition, the implementation of QRIS has had a positive impact on achieving PBB revenue targets. This system supports real-time monitoring, minimizes recording errors, improves administrative efficiency, and encourages taxpayer compliance. Digitizing payments through QRIS also strengthens transparency and bookkeeping accuracy, thus assisting the Kediri Regency Bapenda in evaluating revenue performance. The findings of this study confirm that QRIS is an effective solution for improving the convenience of tax services and supporting the optimization of regional revenue.